Gullah Home Cooking the Daufuskie Way : Smokin' Joe Butter Beans, Ol' 'Fuskie Fried Crab Rice, Sticky-Bush Blackberry Dumpling, and Other Sea Island Favorites - Robinson, Sallie Ann (Book collections on Project MUSE., 2003)
""If there's one thing we learned coming up on Daufuskie, "" remembers Sallie Ann Robinson, ""it's the importance of good, home-cooked food."" In this enchanting book, Robinson presents the delicious, robust dishes of her native Sea Islands and offers readers a taste of the unique, West African-influenced Gullah culture still found there. Living on a South Carolina island accessible only by boat, Daufuskie folk have traditionally relied on the bounty of fresh ingredients found on the land and in the waters that surround them. The one hundred home-style dishes presented here include salads an